Biodegradation of pyrene by Pseudomonas sp. ISTPY2 isolated from landfill soil: Process optimisation using Box-Behnken design model. (December 2019) - Swati,; Ghosh, Pooja; Thakur, Indu Shekhar
Abstract: The present study evaluated the potential of a bacterial isolate Pseudomonas sp. ISTPY2, isolated from Ghazipur landfill soil for pyrene degradation. Removal efficiency of pyrene was optimized by using Response Surface Methodology (RSM) and Box-Behnken design (BBD) model. Experiments were performed as a function of pH (2−12), glucose concentration (1–2% w / v ), and inoculum size (0.6–1% w/v). Under optimum process conditions of pH 8.51, 1% w/v glucose concentration and 0.9% w/v inoculum size, a substantial increase in pyrene degradation was observed with 98% pyrene being degraded by 7th day. The Pseudomonas sp. ISTPY2 showed an involvement in both phthalate and naphthalene pathways of pyrene degradation as confirmed by metabolite study. The study ascertained the importance of statistical tools like RSM for enhancing microbial degradation of contaminants. Graphical abstract: Unlabelled Image Highlights: Pyrene was biodegraded using Pseudomonas sp. ISTPY2. Pseudomonas sp. ISTPY2 was an indigenous isolate of the Ghazipur landfill site. The degradation of pyrene was optimized by response surface methodology. Optimized conditions showed enhanced degradation of pyrene up to 98%.